المتغيرات المؤثرة في تقلبات إنتاجية محاصيل الحبوب في محافظة نينوى للموسم 2009-2010 : محصول القمح والشعير أنموذجا - عماد حسن مصطفى (PROSPECTIVE RESEARCHES, 2023)
This study estimates the effect of changing in Rainfall and Fertilizers upon the wheat and barley productivity, using different levels of rainfall in Ninawa during the period of 2009–2010. The main results of the analysis and estimation, show that the increase the rate of rainfall and fertilizers have positive effect in the increase of the hectares productivity of wheat and barley in confidence rain area, while in the sub confidence area, we find the statistical significant effect of rainfall during the growth period, and the effect is positive between fertilizing, and hectares productivity in these areas.